PENERAPAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATERI OPERASI PENJUMLAHAN DAN PENGURANGAN KELAS II SD - yuhanita, Yuhanita Ulzana; Sutrisno Condro Apriyanto; Siti Inganah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the Deep Learning approach compared to the conventional Surface Learning approach in improving students’ understanding of addition and subtraction concepts in Grade II elementary school. The research employed a quantitative method with a Quasi-Experimental Non-Equivalent Control Group Design. The sample consisted of 54 students divided into an experimental class (n = 27) and a control class (n = 27) at SD Muhammadiyah Terpadu Ponorogo. Data were collected using learning outcome tests (pre-test and post-test). Data analysis was conducted using an independent sample t-test. The results show a significant difference between the experimental and control groups, with t-count > t-table (5.42 > 2.00) and a significance value of p < 0.05. The average N-Gain of the experimental class was 0.71 (high category), compared to the control class at 0.35 (medium category). It is concluded that the Deep Learning approach is effective in significantly improving students’ mathematical understanding.